2010 Fifth IEEE Workshop on Wireless Mesh Networks 2010
DOI: 10.1109/wimesh.2010.5507902
|View full text |Cite
|
Sign up to set email alerts
|

Known Interference Cancellation: Resolving Collisions Due to Repeated Transmissions

Abstract: Abstract-Reception of duplicate packets by a node in a wireless network is a common occurrence. Reasons for repeated transmissions range from broadcast flooding to multicast streaming to unicast forwarding. These repeated transmissions may also get involved in collisions like other original transmissions. We argue that when one of the colliding packets is previously overheard, its interference can be cancelled to decode the other packet. In other words, when a receiver overhears a packet, it becomes effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Our results showed that the proposed detection method has better BER performance, compared to conventional channel estimation-based detection method. The proposed method is bandwidth efficient and can be used in any system model where the self-interference signal is known, such as in two-way relay networks and multi-hop one way relay networks [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the proposed detection method has better BER performance, compared to conventional channel estimation-based detection method. The proposed method is bandwidth efficient and can be used in any system model where the self-interference signal is known, such as in two-way relay networks and multi-hop one way relay networks [17], [18].…”
Section: Discussionmentioning
confidence: 99%
“…2, we can see that PNC and FD are different from the proposed E2E-KIC, because they focus on KIC within one or two hops. More application examples of KIC can be found in [4], which also focus on KIC with one or two hops.…”
Section: Related Workmentioning
confidence: 99%
“…We ignore the low-probability event that collision occurs at the two initiating nodes when they are receiving their corresponding CTS frames 4. The terms "nodes" in the three sub-cases mean "nodes except for n i ".…”
mentioning
confidence: 99%
“…When payload size is 512 byte, T com is 3082 s for the case of IEEE 802.11 series standard including average duration of initial backoff. Thus we set T B as 522 s so that its T com is also 3082 s. This setting not only satisfies the requirement given by (9) when the packet format of Fig. 3 is employed, but also makes the absolute traffic for IFIC and CSMA/CA identical for the same G, so that their performance can be fairly compared.…”
Section: B Simulation Conditions For Ific and Csma/camentioning
confidence: 99%
“…Depending on whether or not the bit information contained in the interference signal is required to perform IC, these methods can be categorized into two types, Unknown IC [4] [5] and Known IC [6]- [9]. Successive interference cancellation (SIC) [4], which is a kind of Unknown IC, can extract desired signal even if it is weaker than the interfering signal by making use of capture effect.…”
Section: Introductionmentioning
confidence: 99%